(untitled) (Northern International Medical College Journal, 2016)
Objective : To assess the hygienic practices during menstruation among adolescent school girls in selected secondary rural schools. Methods : This descriptive, cross-sectional study was conducted from November to December, 2015. Study area was selected on choice were four upazilas of Kishoreganj, Lakshmipur, Barguna and Sirajganj District. From the study area 15 schools were selected on the basis of convenience and accessibility. Data were collected from 438 purposively selected adolescent unmarried school girls aged 15-18 years and studying in class IX and X, through face to face interview by pretested questionnaire. Data were analyzed by using software SPSS version 20. Results : The result of the study revealed that majority (52%) participants were using cloths and 48.4% were using sanitary napkin for menstrual hygiene management. About half of the participants got the information about menstrual and reproductive health from family members. Thirty five percent (35%) girls do not attend school during first two days of menstruation. Majority (69%) of the girls never change pad and 45% complained about unavailability of water at school. However, knowledge of reproductive health issues like minimum age at marriage (18yrs, 85.8%), minimum age of child birth (20yrs, 89%) and need for extra nutrition during pregnancy (99.0%) was quite satisfactory. The level of maternal education and economic condition were significantly associated with sanitary napkin use. Conclusion : The study revealed that higher percentage of participants was not using sanitary napkins, although their knowledge regarding menstrual and reproductive health issues is satisfactory. Implementation of school health programs for adolescents should emphasis on menstrual hygiene management. Northern International Medical College Journal Vol.7(2) Jan 2016: 139-142